Greek Art and Archaeology, 1200-30 BC. (Lockwood Press, 2016)
Τhis lavishly illustrated book surveys Greek archaeology from the collapse of the Mycenaean palaces to the subordination of the last Hellenistic kingdoms to Rome. Its aim is to study Greek art through the material record, and against its cultural and social backdrop. The book's target audience is archaeology and art students, as well as anyone interested in Greek art and culture. Through concise, systematic covering of the main categories of classical monuments, the reader is taken to a tour of ancient Greece along the most spectacular period in its history, the 1st millennium BC. Architecture and city planning, sculpture, painting, pottery, metallurgy, jewelry, and numismatics are some of the areas covered.